Polarity-dependent effects of transcranial direct current stimulation in obsessive-compulsive disorder. Issue 1 (2nd January 2016) - D'Urso, Giordano; Brunoni, Andre Russowsky; Anastasia, Annalisa; Micillo, Marco; de Bartolomeis, Andrea; Mantovani, Antonio
Abstract : About one third of patients with obsessive-compulsive disorder (OCD) fail to experience significant clinical benefit from currently available treatments. Hyperactivity of the presupplementary motor area (pre-SMA) has been detected in OCD patients, but it is not clear whether it is the primary cause or a secondary compensatory mechanism in OCD pathophysiology. Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique with polarity-dependent effects on motor cortical excitability. A 33-year-old woman with treatment-resistant OCD received 20 daily consecutive 2 mA/20 min tDCS sessions with the active electrode placed on the pre-SMA, according to the 10–20 EEG system, and the reference electrode on the right deltoid. The first 10 sessions were anodal, while the last 10 were cathodal. Symptoms severity was assessed using the Yale–Brown Obsessive Compulsive Scale (Y-BOCS) severity score. In the end of anodal stimulation, OCD symptoms had worsened. Subsequent cathodal stimulation induced a dramatic clinical improvement, which led to an overall 30% reduction in baseline symptoms severity score on the Y-BOCS. Our study supports the hypothesis that pre-SMA hyperfunction might be responsible for OCD symptoms and shows that cathodal inhibitory tDCS over this area might be an option when dealing with treatment-resistant OCD.